Simulation of coating phase structure formation in solid phase synthesis assisted by electron-beam treatment; Theoretical Foundations of Chemical Engineering; Vol. 42, iss. 4 - Sorokova S. N. Svetlana Nikolaevna (2008, 2008)
Title screen